Assessment of Data Quality in Hospital Reporting on Sumatra Island in 2023 through the RS Online Application - Elfrida, Maura; Kusumaningrum, Panggih Dewi; Pramono, Angga Eko (Universitas Muhammadiyah Sidoarjo, 2024)
One of the uses of technology in the healthcare sector is the implementation of health information systems (HIS). An example of HIS implementation in Indonesia is RS Online. RS Online is part of the hospital information system used for routine hospital reporting by adjusting data and information needs at the Ministry of Health. Data from health facilities, such as hospital data in RS Online, are the main data source for evaluating the performance of the health sector. Data urgency arises due to the importance of data quality and its resulting impacts. The aim of this research is to determine the level of hospital reporting data quality on Sumatra Island in 2023 on the RS Online application. This research was quantitative with a cross-sectional design. The sample consisted of 753 hospitals on Sumatra Island, which was determined by total sampling. The results of routine data quality assessment reached 100% in the uniqueness dimension, 94.59% in the completeness dimension, 98.71% in the accuracy dimension, and 99.52% in the validity dimension. The results show that the routine hospital reporting data quality on the RS Online application in 2023 on Sumatra Island is categorized as good.